Histology for dental students with clinical aspects - Bokariya, Pradeep; Gupta, Abhishek (New Delhi : Jaypee, 2008)
The book presents update and concise account of the complicated yet interesting subject, Histology, for the dental students. It provides a unique pictorial approach to make complexities of tissue structure easier to understand and remember. The most striking attraction of the book is the inclusion of the topics and chapters which are recently incorporated in the DCI curriculum. The language of the text is kept simple and is well suited for a broad range of students including ones having little English background. Color atlas at the beginning of the book featuring good quality photomicrographs elucidates the appearance of various structures more accurately and thus will help the students master the key knowledge in textual presentation. Hand drawn color illustrations which effectively communicate every essential aspect of cell structure and function have been incorporated.
Keywords: Histology; Teeth; Tooth